Multiple membrane extrusion sites drive megakaryocyte migration into bone marrow blood vessels - Brown,E; Carlin,LM; Nerlov,C; Lo,Celso C; Poole,AW (Life Science Alliance, 2018)
Platelets, cells central to hemostasis and thrombosis, are formed from parent cell megakaryocytes. Whilst the process is highly efficient in vivo, our ability to generate them in vitro is still remarkably inefficient. We proposed that greater understanding of the process in vivo is needed and used an imaging approach, intravital correlative light-electron microscopy, to visualize platelet generation in bone marrow in the living mouse. In contrast to current understanding we found that most megakaryocytes enter the sinusoidal space as large protrusions rather than extruding fine proplatelet extensions. The mechanism for large protrusion migration also differed from that of proplatelet extension. In vitro, proplatelets extend by sliding of dense bundles of microtubules, whereas in vivo our data showed an absence of microtubule bundles in the large protrusion, but the presence of multiple fusion points between the internal membrane and the plasma membrane, at the leading edge of the protruding cell. Mass membrane fusion therefore drives megakaryocyte large protrusions into the sinusoid, significantly revising our understanding of the fundamental biology of platelet formation in vivo.